2015
DOI: 10.1017/s1049023x15005385
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital Airway Management in Emergency and Trauma Patients: A Cross-sectional Study of Ambulance Service Providers and Staff in a Low- and Middle-income Country

Abstract: Even though ambulances are equipped with basic equipment, due to lack of trained staff, these ambulances only serve the mere purpose of transportation. There is a need to train ambulance staff and increase ambulance to staff ratio to improve prehospital AM and patient survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Despite this prevalence, training remains limited. A study in Pakistan revealed 64% of ambulance staff interviewed were unfamiliar with AM and had limited awareness of AM in critical situations [34]. Another study found that despite 52% of patients in Iran requiring AM, just 20.8% were managed appropriately, defined by PHTLS guidelines [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite this prevalence, training remains limited. A study in Pakistan revealed 64% of ambulance staff interviewed were unfamiliar with AM and had limited awareness of AM in critical situations [34]. Another study found that despite 52% of patients in Iran requiring AM, just 20.8% were managed appropriately, defined by PHTLS guidelines [17].…”
Section: Discussionmentioning
confidence: 99%
“…With limited research on the state of prehospital AM in resource‐limited settings, the majority of studies included in this scoping review were case–control and retrospective cohort studies (12/17), [13, 14, 17, 27–29, 31, 33, 35, 36, 38, 39] while a limited selection of included studies were observational or qualitative in nature (5/17) [26, 30, 32, 34, 37]. Of the studies meeting inclusion criteria, first responder curricula teaching ABC were most common, found in 11 studies, followed by ET intubation in eight studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten years following Hisamuddin's (39) observations, trauma systems remain undeveloped and unorganised in 'most Asian countries', with the exception being high-income countries (41). This statement is reinforced by a description of Indonesian pre- hospital services as having vehicles with only basic equipment (42) and staffed from Puskesmas (the term in Bahasa Indonesian for a community health clinic) with ambulance nurses lacking pre-hospital skills and knowledge (40).…”
Section: Current Status Of Pre-hospital Data Collection In Malaysia Amentioning
confidence: 99%
“…11 The evidence revealed that until recent years, there was a little study about knowledge and practice of specific staff called Emergency Medical Team (EMT) and still no organized recruitment guideline or formal training available in most developing countries about pre-hospital emergency care. 12 Less than 10% of all violence that led to death occurred in low-income countries due to delay in the emergency care before the hospital settings. 13 The evidence also suggested that the lack of information or knowledge about prehospital emergency care results in 16% dissatisfaction with the care given to the client.…”
Section: Introductionmentioning
confidence: 99%